(untitled) (Fiep Bulletin - online, 2011)
ABSTRACT The objective in this study was to assess the motor perceptive profile in 30 women aged between 60 and 65 subjected to a sound rhythmic task. The Rhythm Pattern Test (RPT), developed by BUONO (2001), was used as assessment strategy. The data were assessed through the descriptive statistics, counting on the test t with significance p < 0,05. Based on the data, it’s possible to conclude, as for the elderly women’s performance, low speed reaction predominance in relation to sensory stimulation, central process slowing down and the discrimination capacity decreasing when the motor perception is associated with a sound rhythmic task.